DISKURSUS SOSIOLOGI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Muhamad Huda, Dwi Sakti; Ahmad Syaiful, Dodi Alaska; Wahyuni, Desi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The Constitutional Court Decision Number 46 / PUU-VIII / 2010 annulled the provisions of Article 43 paragraph (1) of the Marriage Law because it contradicts the 1945 Constitution of the Republic of Indonesia and does not have binding legal force. The legal reason behind the rechtfinding is to emphasize that children born outside of marriage have the right to legal protection. This research was conducted with the aim of knowing the impact of the Constitutional Court Decision Number 46 / PUU-VIII / 2010 on one of the judges' judicial duties. This study uses a socio-legal approach with data collection techniques for study documents of literature materials. Based on the results of the analysis of the Constitutional Court Decision Number 46 / PUU-VIII / 2010, it does not contradict and intersect with the sociological discourse in accordance with the argumentum a contrario method. Then have coherence between the parental or bilateral kinship system with the Constitutional Court Decision No. 46 / PUU-VIII / 2010 in its application in Indonesia. This condition demands the intellectuality of Judges who are required to think on a broad scale and consider other disciplines in their legal findings.